2014
DOI: 10.1016/j.scitotenv.2013.10.125
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene passive samplers to determine sediment–pore water distribution coefficients of persistent organic pollutants in five heavily contaminated dredged sediments

Abstract: To cite this version:Benoit Charrasse, Céline Tixier, Pierre Hennebert, Pierre Doumenq. Polyethylene passive samplers to determine sediment-pore water distribution coefficients of persistent organic pollutants in five heavily contaminated dredged sediments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…The sample was then sonicated for 30 minutes and placed on a hot plate (130℃) until it was almost dry. Next, HNO 3 and HF were put into the tank at a ratio of 1:1 and covered with the lid. Finally, the tank was placed into an air oven overnight at a temperature of 170℃.…”
Section: Heavy Metal Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was then sonicated for 30 minutes and placed on a hot plate (130℃) until it was almost dry. Next, HNO 3 and HF were put into the tank at a ratio of 1:1 and covered with the lid. Finally, the tank was placed into an air oven overnight at a temperature of 170℃.…”
Section: Heavy Metal Determinationmentioning
confidence: 99%
“…Researchers have found that great quantities of contaminated sediment exist in organic compounds (Charrasse et al, 2014). The water quality in most cities has deteriorated, and the rivers into which much of the wastewater is deposited has become malodorous, This is due to the high level of alluvial-contaminated sediment which remains in the water long after the pollutants have been introduced (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The apparent distribution coefficients (K d ) defined as the total sediment concentration (C s ) to the water concentration (C w ) ratios are calculated from the analysis performed by accelerated solvent extraction (according to Belles et al (2016a)) for C s and from the experiment of PS equilibration for C w (Lohmann et al, 2005;Charrasse et al, 2014). If K d provides quick and easy information for predicting the distribution of pollutants between the water and the solid phase, it suffers from lack of precision because it does not take into account the PAH not freely exchanged between the dissolved and sorbed states.…”
Section: Distribution Coefficientsmentioning
confidence: 99%
“…They used PAH, as in the present study, because of their apolar characteristics. In the same way, Charrasse et al (2014) investigated sediment pore water partition in agitated sediment monitored by LDPE.…”
Section: Introductionmentioning
confidence: 99%